The use of Filmic Text in English Language Classes: Beyond Emotions a Study Carried out in a Brazilian Public School (Global Journal of Human-Social Science, 2021)
This paper is an excerpt from a Master's thesis entitled "The use of the filmic text during English Language classes: an interface with secondary-graders' emotions" and focus on presenting the contributions resulting from the use of a filmic text in English classes, and how the students' emotions can interfere in the learning process. The research was conducted in a second grade of a public high school in city of Araguaína -northern Brazil. It was an interventionist research, with qualitative basis and interpretative nature. Considering the use of filmic text in English classes, we will present the significant advances of the students in their learning with regard to the practices aimed at listening comprehension, pronunciation, reading and writing in English. Hence, these activities helped students to overcome shyness, shame, nervousness and fear besides contributing for elicit positive emotions such as joy and interest during the classes.
Keywords: textual genre; filmic text; emotions